DIFFICULTIES IN ENGLISH GRAMMAR INSTRUCTION (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article analyzes the main problems encountered in teaching English grammar to students of technical polytechnics. The causes of the problems are identified, modern pedagogical approaches and innovative methods are proposed to eliminate them. The article highlights the importance of the communicative approach, the use of technological tools and contextual teaching, and shows ways to effectively organize grammar lessons. The results of the study serve as an important basis for increasing motivation and developing practical skills in the process of teaching English.